Train the Trainer—November 2014 - A Seminar Report by Bob Blair and Grazia Gatti, United Kingdom (Homœopathic Links, 2015)
This report is on the first Teacher Training Course that was organised in November 2014 by The Other Song International Academy for Advanced Homeopathy in Mumbai.
Keywords: Sensation method; Synergy approach; Education; Teacher training course